The effects of regulated short selling on stock returns of affected companies - Siti Munirah, Baharuddin (2017)
Short selling is an investment technique that allows an investor to sell stocks which he does not own currently and buy later at possibly a lower price in Malaysia, short selling trading was prohibited effectively from 5th September 1997 for the purpose of stopping speculation on stock during 1997 Asian Financial Crisis. Short selling activities were commonly designed or structured by local regulators, financial intermediaries, and investors for purposes of managing risks, increasing liquidity and strengthening market infrastructure. There is a lack of study on short selling in Malaysia, hence, this study focuses on "Regulated Short Selling (RSS)" in Malaysia and concentrates on stock price fluctuation on announcements of either a stock is being added into or withdrawn from the RSS list by Bursa Malaysia (BM). 1n this case, we could investigate whether short selling is welcomed by investors. A total of 259 stocks to be added into RSS list and a total of 121 stocks to be withdrawn from RSS list were retrieved from 2013 to 2016. Average abnormal return (AAR) and cumulative average abnormal return (CAAR) were taken to test on hypothesis in this study. The findings show that prices of stocks go up following the announcements of adding the stocks to the RSS list, stock prices would change surrounding the effective dates after it is added into the RSS list, and stock exclusions influence prices negatively on effective dates. Based on this research, to earn abnormal profits, an investor could try to predict RSS additions or removals by BM.